URGENSI PENGELOLAAN WAKTU DALAM TINJAUAN PENDIDIKAN ISLAM MADRASAH IBTIDA`IYAH - Noprijon, Noprijon; Kustanti, Martin; Sepriyanti, Nana (Elementar : Jurnal Pendidikan Dasar, 2024)
Time management has important benefits in the review of Islamic education, because it is important to set a priority scale so that all activities are truly allocated according to the time needed. In addition, minimizing all forms of possible obstacles that will arise in the implementation of Islamic education is also an effective strategy in managing time. In essence, the arrangement of time in such a way in learning in Islamic education according to existing programs and activities can facilitate efforts to achieve goals optimally. This study uses library research. Library research is a literature study conducted using relevant and available reading sources, which are related to the topics discussed in the study. The results of this study are Time Management, so it can be concluded that time management is the ability to use time effectively and efficiently to obtain maximum benefits. The principles of time management in Islamic Education are; (1) prioritizing important tasks; (2) making plans and schedules properly; (3) managing time wisely; and (4) building positive habits. The urgency or importance of time management at Madrasah Ibtida`iyah Nagari Lakitan Tengah, West Sumatra is; (1) time management helps achieve goals; (2) time management helps students and teachers be more organized; and (3) good time management helps to make the heart calmer and better. In conclusion, the importance of time management at Madrasah Ibtida'iyah Nagari Lakitan Tengah, West Sumatra, with good time management a good learning atmosphere will be created, good learning conditions will create high teaching motivation which will ultimately reflect a teacher who is able to carry out learning professionally.